Utilization of Date palm (Phoenix dactylifera L.) wastes for bioethanol production using Pichia kudriavzevii strains - Folake T. Afolabi; Ibukun E. Ola (Novel Research in Microbiology Journal, 2022)
Tons of Date palm (Phoenix dactylifera L.) fruit wastes are discarded daily by the date palm processing industries thus leading to serious environmental problems. This study aimed to investigate the potential of date palm fruit wastes as sugary feedstock for bioethanol production using yeasts. Proximate analysis of the date fruit wastes revealed a moisture content of 8.98 %; crude protein (4.39 %), ash (2.35 %), fat (0.2 %), fiber (0.8 %) and carbohydrate (84.28 %). Sulphuric acid was used for pre-treatment of the date palm fruit substrate. Fermentation was carried out under shaking and static conditions using Pichia kudriavzevii yeast strains isolated from date palm fruit wastes. Greater bioethanol yield was observed when the substrates were fermented under shaking condition. Optimization of the physical conditions improved the fermentation process faster, and significantly enhanced the production of bioethanol. An appropriate temperature of 30oC and pH 5 produced high yield of ethanol (5 %) by Pichia kudriavzevii SGD21, whereas pH 6 for Pichia kudriavzevii SGD30 recorded a higher ethanol yield of 6 %. Under the optimal physical conditions, the fermentation process resulted in the production of 4 % ethanol after an incubation period of 96 h. Moreover, the Pichia kudriavzevii strains could be recommended for bioethanol production at 30 % inoculum size, on using sucrose as a carbon source and yeast extract as a nitrogen source. On using the Fourier-Transform Infrared (FTI) spectroscopy, the detected functional group of the produced bioethanol was O-H group. Finally, utilization of date palm fruit wastes and the yeasts strains of Pichia kudriavzevii SGD21 and Pichia kudriavzevii SGD30 can be exploited for bioethanol production and this could be an effective way for management and utilization of date palm fruit wastes.